Quantitative Synthesis of Research Evidence: Multilevel Meta-Analysis. (August 2019) - Moeyaert, Mariola
Multilevel meta-analysis is an innovative synthesis technique used for the quantitative integration of effect size estimates across participants and across studies. The quantitative summary allows for objective, evidence-based, and informed decisions in research, practice, and policy. Based on previous methodological work, the technique results in powerful, unbiased, and precise effect size estimates. However, its use in practice is limited and its full potential is not yet fully understood. This article aims to bring the multilevel meta-analytic model closer to the applied researcher by introducing the technique at a conceptual level and discussing its full potential and relevance to the field. The procedure of multilevel meta-analysis is illustrated using a recent single-case meta-analytic dataset. Software codes, output tables, interpretations, and graphical displays of effect size estimates are given such that the reader can repeat the analysis independently.